2018 IEEE 37th International Performance Computing and Communications Conference (IPCCC) 2018
DOI: 10.1109/pccc.2018.8711321
|View full text |Cite
|
Sign up to set email alerts
|

U-PoT: A Honeypot Framework for UPnP-Based IoT Devices

Abstract: The ubiquitous nature of the IoT devices has brought serious security implications to its users. A lot of consumer IoT devices have little to no security implementation at all, thus risking user's privacy and making them target of mass cyber-attacks. Indeed, recent outbreak of Mirai botnet and its variants have already proved the lack of security on the IoT world. Hence, it is important to understand the security issues and attack vectors in the IoT domain. Though significant research has been done to secure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…These devices are at risk of being used for attacks. 36,37 DNVRS-Webs is used for IoT devices, including webcams and DVRs, and its vulnerabilities also provide good opportunities for attackers. 38 In summary, we believe that the Mozi samples make full use of the ports and server vulnerabilities described above to attack and infect devices, making the Mozi botnet continue to expand.…”
Section: Device Compositionmentioning
confidence: 99%
“…These devices are at risk of being used for attacks. 36,37 DNVRS-Webs is used for IoT devices, including webcams and DVRs, and its vulnerabilities also provide good opportunities for attackers. 38 In summary, we believe that the Mozi samples make full use of the ports and server vulnerabilities described above to attack and infect devices, making the Mozi botnet continue to expand.…”
Section: Device Compositionmentioning
confidence: 99%
“…Similarly, Ref. [26] introduces a honeypot which uses Universal Plug and Play (UPnP) protocol. The honeypot is freely available under open-source license and it emulates real IoT devices.…”
Section: Honeypots For the Iot Networkmentioning
confidence: 99%
“…Their results from 120,000 hosts indicated that merely 35 % had an UPnP enabled router. Related to our honeypot implementation, Hakim et al [30] introduced a concept of generating UPnP honeypots based on UPnP description files.…”
Section: A Nat Traversal Protocolsmentioning
confidence: 99%